2013
DOI: 10.1016/j.jpedsurg.2013.03.025
|View full text |Cite
|
Sign up to set email alerts
|

Multiphoton microscopy to identify and characterize the transition zone in a mouse model of Hirschsprung disease

Abstract: Background The distribution of ganglion cells in the transition zone of Hirschsprung Disease (HD) colons is extremely variable. Determining the resection margin based on intraoperative biopsies may be imprecise. Multiphoton microscopy (MPM) is a novel imaging technology with the ability to visualize tissues in real time. In this study, we evaluate the potential of MPM to quantify ganglion cells in a murine model of HD. Methods After IACUC approval, formalin-fixed colons from 7 wild type (WT) and 6 Endothelin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 23 publications
(26 reference statements)
0
7
0
Order By: Relevance
“…45 Although ganglion cells derive from vagal and sacral sources of neural crest cells, and possibly nonneural crest cells, 46 experimental animal models suggest that the final rostral-to-caudal distribution of ganglion cells generally correlates spatially with the rostral-to-caudal extent of intestinal colonization by vagal crest. 47 A TZ is present in these models, 48,49 and many exhibit variable expressivity comparable to that observed in humans. [50][51][52] This phenotypic variation indicates that genetic alterations that predispose to HSCR effect a spectrum of severity that includes distal hypoganglionosis with no aganglionic segment.…”
Section: Variable Penetrance and Expressivity Of Hscr In Animal Modelmentioning
confidence: 52%
“…45 Although ganglion cells derive from vagal and sacral sources of neural crest cells, and possibly nonneural crest cells, 46 experimental animal models suggest that the final rostral-to-caudal distribution of ganglion cells generally correlates spatially with the rostral-to-caudal extent of intestinal colonization by vagal crest. 47 A TZ is present in these models, 48,49 and many exhibit variable expressivity comparable to that observed in humans. [50][51][52] This phenotypic variation indicates that genetic alterations that predispose to HSCR effect a spectrum of severity that includes distal hypoganglionosis with no aganglionic segment.…”
Section: Variable Penetrance and Expressivity Of Hscr In Animal Modelmentioning
confidence: 52%
“…Despite a low quantum yield, AF has often a large emission spectra enabling a collection over a wide range, thus increasing the signal collected. AF of the gut was reported upon mono-(Bhattacharjee et al, 2018) and two-photon excitation (Ricard et al, 2012) in healthy conditions but also for studying pathologies like Hirschsprung’s disease (Aggarwal et al, 2013). Here we used AF to image the ENS and demonstrated that the contrast obtained in our images is not based on a difference of AF emission spectra but rather on a difference of AF intensity of the various structures of the intestinal wall.…”
Section: Discussionmentioning
confidence: 99%
“…Hundreds of fluorophores have action cross-sections that make them amenable to 2P imaging (Ricard et al, 2018) and tissue autofluorescence (AF) can be used to generate intrinsic contrast and provide context information (see, e.g., (Zipfel et al, 2003)). 2P microscopy and AF detection have been used for imaging various parts of the gut, including the stomach (Rogart et al, 2008), the small intestine (Orzekowsky-Schroeder et al, 2011; Ricard et al, 2012) and the colon (Aggarwal et al, 2013). However, these studies used scanning 2PEF microscopy that - like CLSM - is slow, often requiring 6 to 8 s/frame of intestine (see, e.g., (Ricard et al, 2012)) and thus several minutes for imaging a single block of intestinal sample.…”
Section: Introductionmentioning
confidence: 99%
“…Besides cancer, Hirschsprung disease may be another interesting application for in vivo MPM imaging to determine the transition zone between ganglionated and aganglionated bowel 20…”
Section: Discussionmentioning
confidence: 99%